Preliminary vivax malaria vector competence for three members of the anopheles hyrcanus group in the republic of Korea - Joshi D. (2014)
In a study on the comparative susceptibility of Anopheles kleini, An. lesteri, and An. sinensis to Plasmodium vivax, we examined the feeding of laboratory-reared mosquitoes on blood of a patient carrying gametocytes from the Republic of Korea. Sporozoites in salivary glands from day 14 postfeeding were detected in An. kleini and An. lesteri with numbers high enough to initiate infection, while no sporozoites were detected in the salivary glands of An. sinensis. This result suggests that An. kleini and An. lesteri could be vivax malaria vectors in the Republic of Korea. © 2011 by The American Mosquito Control Association, Inc.